Exploring the properties of ultrafiltration membranes with a dynamic layer and bactericidal inoculation for the purification of natural waters - Nechitaylo, Nikolay; Nagornaya, Elena; Nesterova, Elena (Eastern-European Journal of Enterprise Technologies, 2016)
The authors established that with the creation at the surface and in the pore space of membrane of a dynamic layer, there occurs a sharp reduction in the performance efficiency of membranes due to the biological fouling. Biofilms block the outflow thus decreasing the productivity of membranes. In order to eliminate the blocking, it is proposed to introduce biocidal additives to the dynamic layer, which made it possible to decrease the influence of biofouling. The formation of a dynamic layer in the pore space and at the surface of membrane is substantiated with the help of simulation using the filtration equation of Poiseuille. To confirm theoretical positions under laboratory conditions, we developed a procedure for the modification of a flat filter. Next, at a semi-industrial installation we conducted a comparison of operation of membranes with a biocidal additive, without it and with a periodic washing by sodium hypochlorite. The membrane with a biocidal inoculation at the surface demonstrated a stable work at the highest efficiency. Testing at flat membranes may be used as an express method for evaluating the modifying properties of different compositions of additives. This makes it possible to rapidly estimate effectiveness of different compositions of reagents for the surface modification of any type of filters. Specific productivity of the membrane with a modified layer without a biocide treatment reached 58 l×m2/h, of the membrane with a periodic treatment – 97,5 l×m2/h, while the membrane with a modified layer and a bactericidal inoculation demonstrated a more stable performance and its productivity in seven days amounted to 89 l×m2/h. The proposed technology enables obtaining water with the required quality via one-stage treatment, which considerably simplifies the process of water preparation.